Kajian Ilmu Hadis di Asia Tenggara: The Study of Hadith Scholarship in Southeast Asia - Abdullah Muhammad Yusran; Muhammad, Muhammad; Arya Syahputra (Pusat Penelitian dan Pengabdian masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2025)
This article discusses the development of Hadith studies in Southeast Asia, emphasizing the historical transmission, intellectual networks, and academic transformation of the discipline. The study aims to analyze the condition and progression of Hadith scholarship in the region and to explore the contribution and dedication of Southeast Asian scholars in preserving and advancing the field. Using a qualitative approach through library research, this study examines classical and contemporary literature, including the works of early scholars such as Nuruddin ar-Raniri, Abd ar-Rauf al-Fansuri, and Mahfudz at-Tarmasi, as well as recent institutional developments in Indonesia, Malaysia, and Brunei Darussalam. The findings reveal that Hadith studies in Southeast Asia evolved from traditional oral transmission and pesantren-based education into a more systematic and academic discipline in higher education institutions. Moreover, the integration of modern methodologies—such as hermeneutical, contextual, and digital approaches—demonstrates the adaptability of Hadith studies to current scientific and societal challenges. This research contributes to Islamic studies by providing a comprehensive understanding of the continuity and renewal of Hadith scholarship in the Southeast Asian intellectual landscape.